Affirmative Policy A Necessity for Fulfilling the Political Rights of Persons with Disabilities - Pane, Erina; Yanis, Tryan Zaki Aulia (Constitutionale, 2023)
Persons with disabilities have political rights. The right to vote and the right to be elected in general elections. This article examines the political rights of persons with disabilities to be elected in general elections. This is important because the representation of persons with disabilities in the public sphere will voice the rights of persons with disabilities. The purpose of this research is to identify the factors that influence the lack of fulfillment of these political rights for persons with disabilities and to examine the fulfillment of their political rights through affirmative policies. The method used in this research is qualitative with a descriptive analytical approach. Primary data was obtained through in-depth interviews with several informants. Factors contributing to the lack of fulfillment of the political rights of persons with disabilities include education level, welfare, and lack of support from the environment and family. Affirmative policies can serve as an alternative to represent persons with disabilities in the public sphere.